Chronos and the moires. Readings on temporality in greek mythology - Fernández Guerrero, Olaya (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This article is based on two notions of temporality, the circular one and the linear one. From a hermeneutical approach, it traces the presence of both concepts of time in two Greek myths: Chronos (who represents the cosmic and natural time) and the Three Moires (who represent human, limited time). There is also an analysis of two other mythological characters, Mnemosyne and Dionysus, as they refer to two different possibilities of making changes in the time arrow. Greek Mythology, Hermeneutics, Philosophy, Time